Численность и биотопическое распределение лугового и черноголового чеканов на территории Северо-Восточной и Восточной Украины - Баник, М. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
The numbers and habitat distribution of Whinchat (Saxicola rubetra) and Common Stonechat (S. torquata) were analysed for the great part of their ranges' overlap in North-Eastern and Eastern Ukraine.